Proliferation of Peripheral Blood-derived Endothelial Progenitor Cells from Stable Angina Subjects - Yudi Her Oktaviono; Djanggan Sargowo; Mohammad Aris Widodo; Yanni Dirgantara; Angliana Chouw; Ferry Sandra (The Indonesian Biomedical Journal, 2014)
BACKGROUND: A population of circulating Endothelial Progenitor Cells (EPCs) has been reported to play important role in maintaining endothelial function and integrity. Since EPCs culture is crucial and an optimized medium is currently available. Therefore we conducted a study to investigate whether stable angina subjects peripheral blood-derived EPCs could be cultured in this medium. Here, we performed study to detect EPCs characteristics and extracellular signalregulated kinase (Erk)1/2 Mitogen-Activated Protein Kinase (MAPK) pathway as possible underlying pathway for EPCs proliferation.METHODS: Peripheral blood EPCs from 8 stable angina subjects were cultured in an optimized medium with/without addition of supplement for 1 or 3 days. Then, the membrane of cultured EPCs were detected with immunofluorescence method for CD34, Vascular Endothelial Growth Factor Receptor 2 (VEGFR-2) and CD133. Colony forming unit (CFU) enumeration was performed. XTT Cell proliferation assay was performed to assess EPCs growth after 1 and 3-days culture. The western blot analysis was performed to detect possible activation of Erk1/2 MAPK.RESULTS: Number of EPCs and CFU cultured for 3 days were significantly higher than the ones cultured for 1 day (p=0.012). EPCs membrane markers from stable angina subjects were detected as well as CFUs were formed. There were significant increase of EPCs number, CFUs number and phosphorylated-Erk2 amount when the groups with and without supplement were compared (p<0.05). Meanwhile U0126, a MAPK Erk1/2 (MEK1/2) inhibitor, significantly inhibited the supplement-induced EPCs number, CFUs number and phosphorylated-Erk2 amount (p<0.05).CONCLUSION: Our results showed that ERK2 MAPK signaling pathway might play an important role in supplement-induced peripheral blood EPCs proliferation in subjects with stable angina.KEYWORDS: endothelial progenitor cell, EPC, p42, Erk2, proliferation